Osvežitev spomina na znamenite Slovence v Gradcu - Karničar, Ludvik (Slavia Centralis, 2020)
The author of the article emphasizes the importance of refreshing the memory of famous Slovenes in Graz, e.g. Janez Nepomuk Primic, Gregor Krek and Karel Štrekelj.